Penilaian Air Minum Isi Ulang Berdasarkan Parameter Fisika dan Kimia di dan luar Jabodetabek Tahun 2011 - Adelina, Rosa; Winarsih, Winarsih; Setyorini, Herni Asih (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
Quality drinking-water is human basic need in life. Jabodetabek as concentrated resident and industrial area, can’t supply drinking-water need so we need alternative source such as refill drinking water. Health Minister has been assigned quality drinking-water parameters whichis if one of the parameter out from criteria value so the drinking-water not feasible. Pharmacy Laboratory of NIHRD do routine test per year for drinking water. Some of the sample is refill drinking water that applied by community or refill drinking water seller. This article described the result of feasibility study of refill drinking-water on 2011. The design of this study is cross sectional study. The data comes from refill drinking-water test in and out Jabodetabek which applied by community to get feasibility certificate of drinking water in Pharmacy Laboratory, Biomedical and Basic Health Technology Center in January until November 2011. The data was analyzed by descriptive statistic in STATA 9. A hundred and thirty-nine (139) refill drinking-water comes from in and out Jabodetabek. From this data, 105 (75,5%) sample was feasible to drink. There are two variable which cause samples didn’t feasible to drink, Manganese level and degree of acidity value (pH).There is one sample which has Manganese level above maximum level and 33 (23,6%) samples have pH value below 6,5. Most of the refill drinking-water samples feasible and fulfill requirement of physical and chemical paremeters, except Manganese level and pH value. The best filter methods in this study is hexagonal method